Modelling biomacromolecular assemblies with continuum mechanics. (1st April 2015) - Hanson, Benjamin; Richardson, Robin; Oliver, Robin; Read, Daniel J.; Harlen, Oliver; Harris, Sarah
Abstract : We have developed a continuum mechanical description of proteins using a finite element algorithm which has been generalized to include thermal fluctuations and which is therefore known as fluctuating finite element analysis (FFEA). Whereas conventional molecular dynamics (MD) simulations provide a trajectory in which each individual atomic position fluctuates, a FFEA trajectory shows how the overall shape of the protein changes due to thermal agitation. We describe the theoretical background to FFEA, its relationship to more established biomolecular modelling methods and provide examples of its application to the mesoscale biomolecular dynamics of the molecular motor dynein.